Karakteristik Selai Lembar Rumput Laut (Eucheuma Cottonii) Dengan Penambahan Komposisi Gula - Surya Lencana; Rodiana Nopianti; Indah Widiastuti (Jurnal FishtecH, 2018)
The purpose of this research were to know the formulation  and to know the physicochemical of the making of seaweed sheet jam (Eucheuma cottonii) The research was conducted on December 2016 until April 2017. This research method used Randomized Block Design (RBD). The sugar treatment on sheet jam consisted of 50%, 40% and 30%. The parameters of this research were chemical analysis such as water content, ash content, fat, carbohydrate, and coarse fiber while for physical analysis consisted of sensory analysis (color, taste, appearance, flavor and texture). The treatments significantly affected the chemicals parameters such as water and carbohydrate level. The treatments not affected the sensory parameters The water content of seaweed sheet jam produced between 43.78% to 56.52%, ash ranged from 0.26% to 0.57%, fat ranged from 0.2% to 0.27%, carbohydrate ranged from 4.37% to 9.13%. Flavors range from 4.76 (neutral) to 5.4 (like lightly). The best treatment of this research is A1 with 50% of sugar